Human Rights in the Ethical Protection of Youth in Social Networks- The Case of Colombia and Peru - Espinosa Vera, Jefferson Stewart (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2017)
This work analyzes incidents of information technology and communications in the sphere of freedoms beginning with social contemporaneous changes. Later it will analyze the problems with chat and young people in the environment of parental education in the new technologies. Likewise, you can observe the importance of the legislation trying to protect kids, young people, and adolescents in their freedom, integrity and sexual development that can be made vulnerable by cyber criminals that look through different portals of the internet, to trick this special class of our population that must be protected constitutionally and criminally. Looking at this cyberspace framework that has revolutionized the world; and to be someone who uses it daily, it is of vital importance to have special care with children in respect to the use of this type of advanced technological tool, the role that parents, tutors, and society play is of great importance such that, they should grant space spaces where the youth can be guarded or guided to prevention so they don’t become victimized by cyber-crime. Also one of our points will speak of the risks associated with the web, INFOethics, parental education, and especially the general situation with regards to legislation in Colombia and Peru, as it is urgent that both countries take established and preventative measures with regards to the criminal law of each state, due to the vulnerable intimacy of social networks, and therefore because what is most being affected is the youth, which gravely affects their psychosomatic and social development, because there does not exist a correct or suitable use for cyberspace.